Characterization of hot processing parameters of powder metallurgy TiAl-based alloy based on the activation energy map and processing map. (5th December 2015) - Sun, Yu; Wan, Zhipeng; Hu, Lianxi; Ren, Junshuai
Abstract: The hot deformation behavior of powder metallurgy Ti–47Al–2Nb–2Cr alloy was studied by using the activation energy map and processing map in this work. The isothermal compression tests were performed over a range of temperatures 950–1200 °C and strain rates 0.001–0.1 s − 1 on a Gleeble-1500D hot working simulator. The hot working flow behavior and softening of flow stress were discussed. The variation of calculated Q value with hot processing parameters has been presented, it was found that the Q value increases with increasing temperature and strain rate on the whole. Based on the constructed processing maps, the optimal hot processing window of this alloy corresponds to the temperature range of 1025–1075 °C and the low strain rate of 0.001–0.004 s − 1, with a peak efficiency of 55% at 1050 °C/0.001 s − 1 . Meanwhile, the instability maps were developed with the help of the comparison between Murty and Prasad instability criteria. The instability domain that should be kept away is located at high strain and strain rate higher than 0.01 s − 1 for the whole deformation temperature. Both of the optimal process conditions and the predominant flow instability mechanism of PM TiAl-based alloy were validated by microstructure observation involving DRX refined microstructure and cracking, respectively. Graphical abstract: Highlights: Hot deformation behavior of TiAl-based alloy is studied by using flow stress curves. The softening mechanism of alloy is mainly attributed to dynamic recrystallization. The deformation activation energy varies with temperature and strain rate. Stable and instable regions have been identified by the microstructure observation.